If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -9)(x + -4) = 0 Reorder the terms: (-9 + x)(x + -4) = 0 Reorder the terms: (-9 + x)(-4 + x) = 0 Multiply (-9 + x) * (-4 + x) (-9(-4 + x) + x(-4 + x)) = 0 ((-4 * -9 + x * -9) + x(-4 + x)) = 0 ((36 + -9x) + x(-4 + x)) = 0 (36 + -9x + (-4 * x + x * x)) = 0 (36 + -9x + (-4x + x2)) = 0 Combine like terms: -9x + -4x = -13x (36 + -13x + x2) = 0 Solving 36 + -13x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (4 + -1x)(9 + -1x) = 0Subproblem 1
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Subproblem 2
Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9Solution
x = {4, 9}
| 2(x-18)+6(x+2)=x+4 | | 3*5+3*6= | | 3*(5+6)= | | 10x-8x-3x=0 | | x^2+21x-38=0 | | 3x(5+6)= | | 8s+3s=44 | | -32+9=-14-11x | | 4x+5x-12=(-3x)+24 | | (x-7)2=9 | | 45=x-4x | | -6x+24=54 | | -5+z=14-37 | | -9.4x=47.0 | | -5+2=14-37 | | x+5-8=-4 | | -4x^2+24=32 | | -7(3b+3)+(22b-4)=0 | | 9(2x-6)=3(6x+5) | | n-3n=-14-4n | | 9+3z-3=9z+12-3z | | 9+3z-3=9z+122-3z | | 3.9q-1.9-4.3q=-1.4q-5.5 | | 5(5+t)-3(t-6)= | | x(5x+1)(x-9)=0 | | 3(2n-7)+7(4-2n)= | | x^2-6x+20=0 | | 124-6x=21x+16 | | 3/2(5x-2)=x | | 3(x+4)+2(5x+2)= | | 6x+7+3x+1= | | -4x+5=5-4x |